2017
DOI: 10.1038/ncomms14789
|View full text |Cite
|
Sign up to set email alerts
|

A natural tandem array alleviates epigenetic repression of IPA1 and leads to superior yielding rice

Abstract: Super hybrid rice varieties with ideal plant architecture (IPA) have been critical in enhancing food security worldwide. However, the molecular mechanisms underlying their improved yield remain unclear. Here, we report the identification of a QTL, qWS8/ipa1-2D, in the super rice Yongyou12 (YY12) and related varieties. In-depth genetic molecular characterization of qWS8/ipa1-2D reveals that this newly identified QTL results from three distal naturally occurring tandem repeats upstream of IPA1, a key gene/locus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
131
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(131 citation statements)
references
References 39 publications
0
131
0
Order By: Relevance
“…In rice, several genes, including MONOCULM 1 and two WUS orthologs ( TILLERS ABSENT1 and MONOCUM 3 ), regulate tillering (Lu et al ., ; Tanaka et al ., ). Notably, the SQUAMOSA PROMOTER BINDING PROTEIN‐LIKE ( SPL ) family gene OsSPL14 , also known as IDEAL PLANT ARCHITECTURE1 ( IPA1 ), is a key regulator of ideal rice architecture and high rice yields (Jiao et al ., ; Miura et al ., ; Zhang et al ., ). IPA1 is targeted by the microRNA (miRNA) OsmiR156 , which is an upstream master regulator of ideal plant architecture (IPA) in rice.…”
Section: Introductionmentioning
confidence: 97%
“…In rice, several genes, including MONOCULM 1 and two WUS orthologs ( TILLERS ABSENT1 and MONOCUM 3 ), regulate tillering (Lu et al ., ; Tanaka et al ., ). Notably, the SQUAMOSA PROMOTER BINDING PROTEIN‐LIKE ( SPL ) family gene OsSPL14 , also known as IDEAL PLANT ARCHITECTURE1 ( IPA1 ), is a key regulator of ideal rice architecture and high rice yields (Jiao et al ., ; Miura et al ., ; Zhang et al ., ). IPA1 is targeted by the microRNA (miRNA) OsmiR156 , which is an upstream master regulator of ideal plant architecture (IPA) in rice.…”
Section: Introductionmentioning
confidence: 97%
“…In this study, we found that the expression of 1-deoxy-D-xylulose-5-phosphate synthase 2 gene ( DXS ) involved in terpenoid anabolism is up-regulated obviously in OE: OsSPL14 transgenic plant, and the GA 3 content increased significantly. Previous research showed that rice plant with high OsSPL14 protein level appeared large panicles and increased plant height (Jiao et al ., 2010; Zhang et al ., 2017), which may attribute to high GA 3 level. Moreover, the other main function of GA is promoting flowering.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an epigenetic change in the OsSPL14 promoter resulted in the same phenotype (Miura et al ., 2010). Moreover, the three tandem repeats in the upstream regions of IPA1/OsSPL14 enhanced an open chromatin configuration and reduced DNA methylation at IPA1/OsSPL14 promoter, resulting in an optimal OsSPL14 expression and ideal plant architecture with proper tiller number and large panicle (Zhang et al ., 2017). While, the ipa1 loss-of-function mutants generated by CRISPR/Cas9 had a dwarf phenotype with increased tiller number (Li et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a promoter‐editing approach to generate various effective alleles using CRISPR/Cas9 has been developed in tomato; this method may be used to generate diverse trait variations for crop improvement directly in elite lines. IPA1 is a key gene in shaping the ideal plant architecture and enhancing the yield of rice . By targeting the cis ‐ and trans ‐regulatory elements/factors of IPA1 using CRISPR/Cas9, scientists could create various ipa1 alleles, including one leading to optimal IPA1 expression and an ideal yield.…”
Section: Conclusion and Looking Forwardmentioning
confidence: 99%